ANALISIS HUKUM TERHADAP KETERLAMBATAN PEMBERITAHUAN PENGAMBILALIHAN SAHAM (AKUISISI) PT. CITRA ASRI PROPERTY OLEH PT. PLAZA INDONESIA REALTY, TBK - Hendrick Daud Sinaga (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2019)
Corporate takeover or acquisition is a legal act performed by a legal entity or natural person to take over the company's shares, by way of purchase of shares or in part or in full from the assets of the company. Provisions for Acquisition are regulated in Law No. 40 of 2007 concerning the Company and Government Regulation No.27 of 1998. Acquisition is one of the efforts made by the company to increase efficiency in the performance of a company sCo that the company becomes more productive in conducting business activities. Acquisition requires a separate mechanism as stipulated in Article 26 Government Regulation Article 29, 30, 15 of Law No. 40 of 2007. One of the legal problems that occur in the acquisition of a company is the delay in reporting the acquisition of shares that need to be reported administratively to the Business Competition Commission as stipulated in Article 29 of Act Number 5 of 1999 j.o Article 6 of Government Regulation No. 57 of 2010. The obscure issue of notifying the takeover of this share was faced by PT. Plaza Indonesia Realty, Tbk, which acquired PT. Citra Asri Property. So the authors conducted a legal analysis related to the issue of delays in the notification of the takeover of shares of PT. Citra Asri Propery by PT. Plaza Indonesia Realty, Tbk based on Case Decision Number: 02 / KPPU-M / 2017.